DAMPAK KEBEBASAN BERPENDAPAT DAN BERINTERAKSI DI MEDIA SOSIAL TERHADAP ETIKA SOSIAL SISWA : STUDI KASUS DI MAS AL FALAH PANCOR DAO (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of social media provides a wide space of freedom for students to express their opinions and interact, but this freedom is not always accompanied by an adequate understanding of social ethics. This study aims to describe the impact of freedom of opinion and interaction on social media on the social ethics of students at MAS Al Falah Pancor Dao, as well as identify the factors that influence it. This study uses a descriptive qualitative approach with a case study method. Data was collected through observation, interviews, and documentation of students and the school. The results of the study show that social media has a positive impact in the form of increasing students' courage in expressing opinions, growing learning motivation, and the emergence of mutually supportive interactions. However, negative impacts are also seen, such as the emergence of sarcastic behavior, rude comments, imitation of content that is not educational, and decreased learning discipline. Factors that affect social ethics include the living environment, circle of friends, interaction in online games, and the type of content that students consume. This study concludes that the formation of social ethics in the use of social media must be carried out through consistent coaching, collaboration between schools and parents, and the cultivation of digital ethics that are contextual with the lives of today's students.